A minimax linear programming model for dispatching rule selection. (July 2018) - Amin, Gholam R.; El-Bouri, Ahmed
Highlights: Introduces a minimax linear programming (LP) model for dispatching rule selection. Suggests a preference voting model for solving the corresponding problem. Identifies dispatching rules that are moderately good in all criteria. Uses an experimental study to show the applicability of the proposed method. Abstract: Dispatching rule selection is an important problem in production scheduling. This paper introduces a minimax linear programming (LP) model for dispatching rule selection in the presence of multiple criteria. The multi-criteria dispatching rule selection problem is first converted into a preference voting system, and a minimax LP model is then introduced for solving the corresponding problem. The advantage of this conversion is that it provides a way to identify dispatching rules that are moderately good in all criteria, rather than selecting dispatching rules that are good respect to only a few variables. An experimental study considering two different production priority settings is used to show the applicability of the proposed method.